78.6k views
5 votes
Multiply

3x^2(4x^2+ 6x – 3)
A 7x^2 + 92 – 6
B 12x4 +180 - 9
C 12x^2 + 182 – 9
D 12x^4 + 18x3 - 9x^2​

User Jamadan
by
6.5k points

1 Answer

5 votes

Answer:

12 x^4 + 18 x^3 - 9 x^2 thus D is the correct answer.

Explanation:

Expand the following:

3 x^2 (4 x^2 + 6 x - 3)

3 x^2 (4 x^2 + 6 x - 3) = 3 x^2 (4 x^2) + 3 x^2 (6 x) + 3 x^2 (-3):

3 4 x^2 x^2 + 3 6 x^2 x - 3 3 x^2

3 (-3) = -9:

3 4 x^2 x^2 + 3 6 x^2 x + -9 x^2

3 x^2×6 x = 3 x^(2 + 1)×6:

3 4 x^2 x^2 + 3×6 x^(2 + 1) - 9 x^2

2 + 1 = 3:

3 4 x^2 x^2 + 3 6 x^3 - 9 x^2

3×6 = 18:

3 4 x^2 x^2 + 18 x^3 - 9 x^2

3 x^2×4 x^2 = 3 x^4×4:

3×4 x^4 + 18 x^3 - 9 x^2

3×4 = 12:

Answer: 12 x^4 + 18 x^3 - 9 x^2

User Robin Hawkes
by
6.1k points